Risk and the limits of governance: Exploring varied patterns of risk‐based governance across Europe. Issue 2 (10th September 2012) - Rothstein, Henry; Borraz, Olivier; Huber, Michael
Abstract Risk‐based approaches to governance are widely promoted as universally applicable foundations for improving the quality, efficiency, and rationality of governance across policy domains. Premised on the idea that governance cannot eliminate all adverse outcomes, these approaches provide a method for establishing priorities and allocating scarce resources, and, in so doing, rationalise the limits of what governance interventions can, and should, achieve. Yet cursory observation suggests that risk‐based approaches have spread unevenly across countries. Based on a comparison of the UK, France, and Germany, this article explores the ways in which, and why, such approaches have "colonised" governance regimes in the UK, but have had much more limited application in France and Germany. We argue that the institutionally patterned adoption of risk‐based governance across these three countries is related to how entrenched governance norms and accountability structures within their national polities handle both the identification and acceptance of adverse governance outcomes.